Discovery and SAR studies of 2-alkyl-3-phenyl-2, 4, 5, 6, 7, 8-hexahydropyrazolo[3, 4-d]azepines as 5-HT7/2 inhibitors leading to the identification of a clinical candidate. (1st January 2021) - Dvorak, Curt A.; Rudolph, Dale A.; Nepomuceno, Diane; Dvorak, Lisa; Lord, Brian; Fraser, Ian; Bonaventure, Pascal; Lovenberg, Timothy; Carruthers, Nicholas I.
Graphical abstract: Abstract: We report here the synthesis and characterization of a dual 5-HT7 / 5-HT2 receptor antagonist 3-(4-Fluoro-phenyl)-2-isopropyl-2, 4, 5, 6, 7, 8-hexahydro-1, 2, 6-triaza-azulene (4j ). 4j is a high affinity 5-HT7 and 5-HT2A receptor ligand having a pKi  = 8.1 at both receptors. It behaves as an antagonist in an in vitro functional assay for 5-HT2A and as an inverse agonist in an in vitro functional assay for 5-HT7 . In a validated in vivo model for central 5-HT7 activity in rats, blockade of 5-carboxamidotryptamine (5-CT) induced hypothermia, 4j shows efficacy at low doses (ED50  = 0.05 mg/kg, p.o., 1 h) and maximal efficacy was observed at 0.3 mg/kg p.o. with a corresponding plasma concentration of ~27 ng/ml. In a validated in vivo model for central 5-HT2A activity, blockade of 2, 5-dimethoxy-4-iodoamphetamine (DOI) induced head-twitches in mice, 4j shows efficacy at low doses with an ED50  = 0.3 mg/kg p.o. Ex vivo receptor binding studies demonstrate that 4j occupied 5-HT2A receptor binding sites in the frontal cortex of the rat brain with an ED50 in good agreement with the ED50 value for central functional effect mediated by 5-HT2A receptor (ED50  = 0.8 mg/kg, p.o., 1 h).